Electric buses: A review of alternative powertrains. (September 2016) - Mahmoud, Moataz; Garnett, Ryan; Ferguson, Mark; Kanaroglou, Pavlos
Abstract: Evidence suggests that the role of electric buses in public transit is important if we are to take steps to reduce climate change and the environmental impacts of fossil fuels. Several electric alternatives are currently operationalized, and the debate about which is most suitable is attracting considerable attention. This article provides a detailed review of various performance features for three categories of electric buses: hybrid, fuel cell, and battery. Economic, operational, energy, and environmental characteristics of each technology are reviewed in detail based on simulation models and operational data presented by various scholars in different contexts. The study develops a holistic assessment of electric buses based on side-by-side comparison of 16 features that best inform the decision making process. The review indicates that the selection process of electric technology is highly sensitive to operational context and energy profile. In addition, it highlights that hybrid buses will not provide a significant reduction in GHG and would be suitable only for short-term objectives as a stepping-stone towards full electrification of transit. Battery and fuel cell buses are arguably capable of satisfying the current operational requirements, yet initial investment remains a major barrier. Overnight Battery Electric Bus is advocated as the most suitable alternative for bus transit contexts given the expected improvements in battery technology and the trend to utilize sustainable sources in electricity generation.